Some aspects of the acute phase response after a marathon race, and the effects of glutamine supplementation - Castell, L. M.; Poortmans, J. R.; Leclereq, R.; Brasseur, M.; Duchateau, J.; Newsholme, E. A. (European Journal of Applied Physiology, 1996)
In two separate studies of the Brussels marathon, using similar protocols, the time course of the changes in the plasma concentrations of some amino acids (glutamine, glutamate, alanine, tryptophan and branched chain amino acids), acute phase proteins and cytokines (interleukins IL-1<alpha>, IL-2, IL-6, tumour necrosis factor type a) was measured in male athletes.